Inquiry-Based Learning Model Assisted by Canva Media on Motivation and Mathematics Learning Achievement - Musabbihan, Musa; Sariyasa; Nyoman Dantes (Universitas Pendidikan Ganesha, 2024)
Mathematics is still considered a subject that is difficult to understand, boring, and scary, so many students' learning outcomes are worrying. This research analyses motivation and achievement in mathematics by applying the inquiry-based learning (IBL) model assisted by Canva media. This research method uses a quasi-experiment with a posttest-only control group design. The research population was 5th-grade elementary school students in 8 schools. The research sample was taken from 6 elementary schools selected using random sampling techniques. Data collection used learning motivation questionnaire instruments and learning achievement tests. Data were analyzed using Anova and Manova. The results showed a difference in learning motivation between the experimental and control classes, with a significance of 0.000. There is a difference in learning achievement between the practical and control classes, with a significance of 0.000. There is a simultaneous difference in motivation and learning achievement between the experimental and control classes, with a significance of 0.000. The conclusion is that the IBL model assisted by Canva-based media has been proven to affect motivation and learning achievement in mathematics for class V students. This research implies that student motivation and learning achievement can be increased using the IBL model assisted by Canva-based media.